Identification of a Stable Hydrogen-Driven Microbiome in a Highly Radioactive Storage Facility on the Sellafield Site - Ruiz-Lopez, Sharon; Foster, Lynn; Boothman, Chris; Cole, Nick; Morris, Katherine; Lloyd, Jonathan R. (Frontiers in Microbiology, 2020)
The use of nuclear power has been a significant part of the United Kingdom’s energy portfolio with the Sellafield site being used for power production and more recently reprocessing and decommissioning of spent nuclear fuel activities. Before being reprocessed, spent nuclear fuel is stored in water ponds with significant levels of background radioactivity and in high alkalinity (to minimise fuel corrosion). Despite these challenging conditions, the presence of microbial communities has been detected. To gain further insight into the microbial communities present on extreme environments, an indoor, hyper-alkaline, oligotrophic and radioactive spent fuel storage pond (INP) located on Sellafield was analyzed. Water samples were collected from sample points within the INP complex, and also the purge water feeding tank (FT) that supplies water to the pond, and were targeted for 16S and 18S rRNA gene sequencing over a period of thirty months. Only 16S rRNA genes were successfully amplified for sequencing, suggesting that the microbial communities in the INP were dominated by prokaryotes. Quantitative Polymerase Chain Reaction (qPCR) analysis targeting 16S rRNA genes suggested that bacterial cells in the order of 10^4-10^6 mL^-1 were present in the samples, with higher loadings rising with time. Next generation Illumina MiSeq sequencing was performed to identify the dominant microorganisms; 16S rRNA gene sequence analysis suggested that 70 % and 97 % of the OTUs, from the FT and INP samples respectively, belonged to the phylum Proteobacteria, mainly from the alpha and beta subclasses. The remaining OTUs were assigned primarily to the phyla Acidobacteria, Bacteroidetes and Cyanobacteria. Overall the most abundant genera identified were Hydrogenophaga, Curvibacter, Porphyrobacter, Rhodoferax, Polaromonas, Sediminibacterium, Roseococcus and Sphingomonas. The presence of organisms most closely related to Hydrogenophaga species in the INP areas, suggests the metabolism of hydrogen as an energy source, most likely linked to hydrolysis of water caused by the stored fuel. Isolation of axenic cultures using a range of minimal and rich media was also attempted, but only relatively minor components (from the phylum Bacteroidetes) of the pond water communities were obtained, emphasising the importance of DNA-based, not culture-dependent techniques, for assessing the microbiome of nuclear facilities.